Analysis of the Combination of Vendor and Consultant Executors Through Risk Management Moderation on Decision Making for the Development of the E-Procurement System at PT XYZ - Muhammad Sahlan; Paidi W.S (Jurnal Indonesia Sosial Teknologi, 2024)
The selection of potential executor combinations is the initial stage in planning the development of an e-procurement system. The aim is to conduct studies and analyze each combination of executor vendors and consultants based on their impact and scale of importance on cost, time, quality, and flexibility. This study will lead to selecting a recommended combination with the least risk value and the most important based on the current conditions of PT XYZ. The method used in this research is a quantitative method with the MANOVA test to assess differences in the influence of each executor combination on costs, time, quality, and flexibility. Next, a risk analysis is carried out using the FMEA method to assess the Risk Priority Index and determine risk mitigation. After that, the best combination of executors is selected based on the risk value and the interest scale. The research results show that there are differences in the influence on cost and quality of all combinations of executors, but different combinations of executors do not have a different influence on time and specificity. The results of the risk analysis show that there are influences of risk management in the relationship between each type of executor on costs, time, quality, and flexibility, which can be seen from the decrease in the Risk Priority Index value for each risk event that has been identified due to risk mitigation. Finally, the results of selecting potential executor combinations using AHP show that combination 8 is the first potential with a value of 0.136, followed by combination 5 in second place with a value of 0.112, and third place is achieved by combination 7 with a value of 0.111. The fourth, fifth, and sixth places are each occupied by Combination 3 with a value of 0.101; combination 2 with a value of 0.098; and combination 1 with a value of 0.097.